(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The author of the article presents the results of the legal and scientific researches analysis of the personnel policy strategy of the National Police of Ukraine in the context of updating administrative and legal principles of protecting human rights and freedoms. The modern challenges and directions of the personnel policy of the National Police of Ukraine in the conditions of social conflicts escalation are determined. It is stated that the improvement of the personnel policy of the National Police in all stages of its hierarchical structure and all its units has recently influenced, first of all, on the administrative and legal status of this state structure, focusing its activities on human rights and freedoms protection as a general state priority. The concept of “personnel policy” of the National Police of Ukraine is considered as a multidimensional process. It is focused on the implementation of legislative, organizational, administrative, research and other bases for the implementation of the main developing issue of the National Police and its structures; the regulation of procedures of structural units functioning and the police department competencies; defining the tasks, functions, rights, and responsibilities of personnel, as well as the responsibility level of police officers. It is determined that the personnel policy of the National Police is implemented through the totality of social functions of governmental institutions and determines the ways and means of provided reforms and the professionalism of their implementation. It is an important factor of the state integrity strengthening and the element of state regulation of the population lives and strategically determined by the general mission of the National Police. It involves promoting the implementation of state policy in the field of combating crime and ensuring public order, the realization of human rights and freedoms, interests of society and the state, the maintenance of public safety and the provision of services to persons in need within the limits of legislation. It is characterized by the general requirements for the competencies, functions, rights, and responsibilities of the personnel, as well as the responsibility level of police officers. According to the modern legislation, the National Police, as well as its separate units should be transparent in their actions, open enough for external control, including public control, its staff should be able to meet the needs of all segments of the population and structures of society in legal protection and maintaining security. It is proved that the ethical principles of the police officers’ activities are determined by the priority in serving the needs of individual citizens and society in the whole, by close cooperation and interaction with the population, territorial communities and public associations based on partnership and aimed at satisfying their needs, following the current legislation of Ukraine. It is determined that the perspective direction of the studied issue is the development of innovative methods and forms of training and advanced training of personnel capable to meet the professional requirements and ethical standards of policing.